Penyuluhan Produk Digital Untuk Masyarakat Untuk Meningkatkan Akses Dan Pemanfaatan Teknologi - Thomas Afrizal; Han Sulaiman; Rahmatika Rahmatika; Nasrulloh Isnain (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. The longer it goes on, the more changes occur in the rapidly evolving world of technology. Humans today are greatly facilitated by activities that are more practical and require less effort. This development occurs in almost all areas of human life, from children to adults. Digital product development can be one solution to improve community welfare. Digital products themselves can take the form of applications, platforms, or systems that can assist people in various aspects of life, such as education, health, economy, and others. However, not everyone in society necessarily knows and understands digital products themselves. Therefore, training and mentoring are needed to increase the community’s digital capacity and develop it according to their needs. Digital product development can also boost the creative economy and open up business opportunities for the community. Therefore, developing digital products can be a strategy to improve community welfare and reduce social inequality. In achieving the objectives of this activity, the implementing team used a counseling/socialization method in an event. The implementing team, acting as tutors, provided knowledge while also assisting the training participants in mastering the training material. This allowed participants to master the material while simultaneously practicing with instructor guidance. The results of this activity show that the partner group, especially the youth organization members, felt happy and helped because they were able to create whatever they focused on in developing a digital product